Wildfire-related smoke inhalation worsens cardiovascular risk in sleep disrupted rats - Martin, W. Kyle; Schladweiler, M. C.; Oshiro, W.; Smoot, J.; Fisher, A.; Williams, W.; Valdez, M.; Miller, C. N.; Jackson, T. W.; Freeborn, D.; Kim, Y. H.; Davies, D.; et al. (Frontiers in Environmental Health, 2023)
As a lifestyle factor, poor sleep status is associated with increased cardiovascular morbidity and mortality and may be influenced by environmental stressors, including air pollution. To determine whether exposure to air pollution modifies cardiovascular effects of sleep disruption, we evaluated the effects of single or repeated (twice/wk for 4 wks) inhalation exposure to eucalyptus wood smoke (ES; 980 µg/m3 for 1h), a key wildland fire air pollution source, on mild sleep loss in the form of gentle handling (GH; 5 s every 30 min for 5 h during rest period) in 12-week-old, male Sprague Dawley rats. Blood pressure (BP) radiotelemetry and echocardiography were evaluated along with assessments of lung and systemic inflammation, cardiac and hypothalamic gene expression, and heart rate variability (HRV), a measure of cardiac autonomic tone. GH alone disrupted sleep, as evidenced by active period-like locomotor activity, and increases in BP, heart rate (HR), and hypothalamic expression of the circadian gene Per2. A single bout of sleep disruption and ES, but neither alone, increased HR and BP as rats transitioned into their active period, a period aligned with a critical early morning window for stroke risk in humans. These responses were immediately preceded by reduced HRV, indicating increased cardiac sympathetic tone. In addition, only sleep disrupted rats exposed to ES had increased HR and BP during the final sleep disruption period. These rats also had increased cardiac output and cardiac expression of genes related to adrenergic function, and regulation of vasoconstriction and systemic blood pressure one day after final ES exposure. There was little evidence of lung or systemic inflammation, except for increases in serum LDL cholesterol and alanine aminotransferase. These results suggest that inhaled air pollution increases sleep perturbation-related cardiovascular risk, potentially in part by increased sympathetic activity.